Christian Louboutin: pés femininos vestidos com distinção - Rudge, Patrícia Bittencourt (2014)
The research examines the enunciation mechanisms from which the identity of the French shoe brand Christian Louboutin is constructed and how it produces experiences from the body that wears the shoes and, thus, feels the contact between them. We equally investigate how this relationship results in a prescriptive way of being in the social. To this end, the chosen corpus includes models of women s shoes, regarded as discursive arrangements. The work consisted in analyzing plastically the shoes by its individualizing traits, in order to grasp what are the values and the strategies chosen by the addresser in the construction of its identity and visibility. For this step, we take from the French semiotics conceived by Algirdas-Julien Greimas the theoretical framework. Using the generative process of meaning and the axiological, narrative and discursive levels, we explain the construction meaning mechanisms of the brand Christian Louboutin and its strategic convincing procedures through manipulative seduction, as well as notions of figurativity and isotopy, in relation to plastic and semantics analysis which receive the conceptual subsidies from Jean-Marie Floch. We also consider the study of interactions between body and fashion presented by Ana Claudia Oliveira and, finally, the postulates of Eric Landowski of a sensitive semiotics and the meaning regimen, built in interaction. The hypothesis is that the act of the body wearing the shoe, the identity projection sustained by the brand evokes a way of being in the world based on the distinction of the body, whose reconfigured posture by wearing Louboutin shoes, allows the user the right to belong and enjoy the benefits of a select and important dominant group, social, economic, cultural and financially. The examination of the corpus shows how the know-how of the creations conceived in Paris, and produced by hand in Italy, edify, by the discourses Christian Louboutin , Made in Italy and Paris , the French system of numbering of shoes, the angulation of the shank, the tall, thin heel, the materiality of leather, metal and lacquer and the chromaticism of red and gold, distinctive attributes to those who bear it in the feet and have it completely repositioned from the imposed body's way of walking. Through brand identity, we conclude that while a subject that donates competence, provides the body a stereotypical female role in the world, whose performance is regulated by belonging to a particular aesthetic and cultural taste recognized symbolically